2019
DOI: 10.1126/science.aaw1620
|View full text |Cite
|
Sign up to set email alerts
|

The geography of biodiversity change in marine and terrestrial assemblages

Abstract: Human activities are fundamentally altering biodiversity. Projections of declines at the global scale are contrasted by highly variable trends at local scales, suggesting that biodiversity change may be spatially structured. Here, we examined spatial variation in species richness and composition change using more than 50,000 biodiversity time series from 239 studies and found clear geographic variation in biodiversity change. Rapid compositional change is prevalent, with marine biomes exceeding and terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
516
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 485 publications
(589 citation statements)
references
References 225 publications
30
516
6
1
Order By: Relevance
“…Finally, a weaker link between assemblage responses and temperature change on land may be due to other factors, such as land-use change and moisture availability, posing stronger constraints on local biodiversity. Nonetheless, the smaller magnitude or slower responses of terrestrial species to temperature change 5,12,15,24,36,37 , combined with the faster rates of warming on land, indicate a potentially higher risk of climatic debt (i.e. response lags) among terrestrial versus marine taxa 3,12,14,19,36,3840 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a weaker link between assemblage responses and temperature change on land may be due to other factors, such as land-use change and moisture availability, posing stronger constraints on local biodiversity. Nonetheless, the smaller magnitude or slower responses of terrestrial species to temperature change 5,12,15,24,36,37 , combined with the faster rates of warming on land, indicate a potentially higher risk of climatic debt (i.e. response lags) among terrestrial versus marine taxa 3,12,14,19,36,3840 .…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses provide a first step towards explaining divergent patterns of assemblage-level biodiversity change across the planet 24,41 . Overall, our results provide strong support the prediction that divergent biodiversity trajectories across latitude may arise as a consequence of global warming, with polar and temperate regions likely acting as “sinks”, and tropical regions as “sources” 6,8,31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the most common metrics used to monitor biodiversity change do not necessarily capture the processes leading to biodiversity change. Although species extinction rates are estimated to be high above background levels globally (Barnosky et al, 2011), several studies have shown that regional-to-local-scale diversity can actually remain stable or even increase with time (Sax and Gaines 2003;Dornelas et al 2014;Vellend et al 2013;McGill et al 2015;Blowes et al 2019;Steinbauer et al 2018). Plot-scale species richness is thought to be strongly controlled by regional species abundance distributions (Supp & Ernest, 2014) .…”
Section: Introductionmentioning
confidence: 99%